Predictive equations for dietary energy are improved when independently developed for dry and wet food which could benefit both the pet and the environment - Jewell, Dennis E.; Jackson, Matthew I. (Frontiers in Veterinary Science, 2023)
Measuring energy availability through metabolizable energy feeding studies is the “gold standard” for establishing metabolizable energy concentration. However, predictive equations are often used to estimate metabolizable energy in dog and cat pet foods. The goal of this work was to evaluate the prediction of energy density and compare those predictions to each other and the energy needs of the individual pets. Feeding studies used 397 dogs and 527 cats on 1028 canine and 847 feline foods. Individual pet results were used as outcome variables. The difference between the average prediction of energy density and the measured metabolizable energy varied from the modified Atwater prediction 4.5%, 3.4% (NRC equations), 1.2% (Hall equations) to the new equations calculated from these data at 0.4%. The average absolute values of the differences between measured and predicted estimates in pet foods (dry and canned, dog and cat) are: 6.6% (Atwater), 5.1% (NRC equations), 3.6% (Hall equations) and 2.3% (new equations). All of these estimates resulted in significantly less variation in the estimate of the food expected to be consumed than the observed variation associated with actual pet consumption to maintain body weight. On average the dogs consumed 747 kilocalories (Kcals) per day (standard deviation 199) while cats consumed 234 Kcals per day (standard deviation 62). When expressed as a ratio of energy consumed to metabolic body weight (weight in kilograms3/4) the within species variation in energy consumed to maintain weight was still high as compared to the energy density estimates variance from measured metabolizable energy. Dogs consumed on average 120 Kcals/(metabolic body weight) with a standard deviation of 24 and cats consumed 70 Kcals/(metabolic body weight) with a standard deviation of 15. The amount of food offered as the central point in a feeding guide, based on the prediction equations, would on average result in an average variance between 8.2% error in the worst case estimate (feline dry using Atwater estimates) and approx. 2% (the new equations in all settings). All predictions had relatively small differences in calculating food consumed when compared to the differences associated with the variation in normal energy demand.